Autobiographical recall triggers visual exploration (Journal of Eye Movement Research, 2014)
Autobiographical recall is thought to rely on the ability to generate a visual image of the remembered event. Neuropsychological studies suggest a relationship between deterioration in visual mental imagery and autobiographical distortions, while neuroimaging data similarly implicate visual brain areas in autobiographical recall. However, neither whether autobiographical retrieval is associated with visual exploration, or not. Our paper aimed to provide such evidence one way or the other. Using an eye tracking system, we recorded eye movements of 40 participants during autobiographical recall and during a control condition in which participants had to count aloud. In both conditions, the participants had to look at a blank screen while their gaze location was recorded by the eye-tracker. Autobiographical recall triggered a lower number of fixations and reduced their duration. In contrast, the number, duration, and amplitude of saccades increased compared to the control condition. Our data suggest that autobiographical recall is characterized by visual processing.